PERDAGANGAN KAKAO DAN PRODUK KAKAO INDONESIA DI PASAR ASEAN+6 - Devi Agustia (Jurnal Bisnis Tani, 2017)
The purpose of this study was to determine the influence of GDP growth in the agricultural sector to the distribution of income and employment opportunities in the agricultural sector of Indonesia, in the period 1996-2014. This study uses secondary data time series (time series), obtained from the Central Statistics Agency (BPS), and related agencies as well as various data published through various scientific papers are considered to have a correlation and relevance to this study. The results showed that the GDP data processing significant at α = 0.050 shown in the p-value of 0.000 or significant at 100 percent confidence interval with a positive effect on employment. Where the coefficient of determination (R2) is 0.9943, meaning that GDP has an impact for 99percent of the agricultural labor opportunities in Indonesia. Meanwhile GDP is significant at α = 0.10 on income distribution shown in the p-value of 0.000 or significant at 100 percent confidence interval with a positive impact on the Gini ratio. Where the coefficient of determination (R2) is 0.99014, meaning that GDP has a 99 percent influence on income distribution in Indonesia.